Multiple Identities in Wide Sargasso Sea by Jean Rhys - Dibelková, Veronika (Univerzita Pardubice, 2013)
The aim of this paper is to provide an analysis of Wide Sargasso Sea, a novel written by Jean Rhys, which depicts the West Indies during the British colonial rule soon after the abolition of slavery. The analysis is focused on the identities in the novel. It follows the shift from slavery in the West Indies and the consequent identity crisis of the individual characters.
Identity v díle Širé Sargasové moře od Jean Rhysové
Keywords: Rhys, Jean; Wide Sargasso Sea; West Indies; Caribbean; identity; colonialism; Creole; Rhysová, Jean; Širé Sargasové moře; Karibik; identita; kolonialismus; Kreolka